2013
DOI: 10.1007/s10853-013-7369-7
|View full text |Cite
|
Sign up to set email alerts
|

The thermal behaviour of glass fibre investigated by thermomechanical analysis

Abstract: A TMA procedure has been developed with the capability of probing the thermal behaviour of glass fibre. A single glass fibre was successfully mounted into TMA fibre configuration and several thermomechanical programmes were carried out over a wide temperature range from 20°C to 900°C. It was found that measured coefficient of linear thermal expansion (CLTE) of boron-free E-glass fibre remained constant below 300°C and the values had an excellent agreement with that found in the literature. At higher temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 19 publications
3
30
0
2
Order By: Relevance
“…Mechanical loss increases and the modulus decreases with increasing water content in glass [89,90]. Interestingly, this would imply that exposure of glass to elevated temperatures could presumably lower the water content and increase the measured modulus (as has been experimentally observed by Yang and Thomason [54]). It has been suggested that water enters into glasses, accelerated by tensile stress and causes swelling, which reduces modulus and strength in a manner similar to the plasticization effect in polymers [88,89].…”
Section: Interaction With Watermentioning
confidence: 64%
See 3 more Smart Citations
“…Mechanical loss increases and the modulus decreases with increasing water content in glass [89,90]. Interestingly, this would imply that exposure of glass to elevated temperatures could presumably lower the water content and increase the measured modulus (as has been experimentally observed by Yang and Thomason [54]). It has been suggested that water enters into glasses, accelerated by tensile stress and causes swelling, which reduces modulus and strength in a manner similar to the plasticization effect in polymers [88,89].…”
Section: Interaction With Watermentioning
confidence: 64%
“…Recent results published by Yang and Thomason [54] provided further evidence of this fibre structural relaxation phenomenon by investigation of the thermo-mechanical properties of single boron-free E-glass fibres. Using a thermo-mechanical analyser, fibre length changes were monitored, and in situ measurement of the fibres Young's modulus was performed.…”
Section: Thermal Compaction or Enthalpy Relaxationmentioning
confidence: 81%
See 2 more Smart Citations
“…The linear composition models cannot account for the structural variations or speciation of the network formers, such as SiO2, B2O3, and Al2O3. Secondly, glass density or molar volume is affected by fictive temperature or thermal history of the samples in terms of glass structure relaxation [42][43][44]. In turn, annealed glass has lower fictive temperature, higher density, and hence, higher Young's modulus as compared to the quenched form of the same glass composition.…”
Section: Young's Modulus Of Glass and Glass Fibersmentioning
confidence: 99%